Pengaruh Kompensasi Terhadap Kinerja Karyawan CV. Mega Anugerah Kudus - Ira Aprilia; Marwan Effendi (Universitas 45 Surabaya, 2024)
Human resources have a major role in a company. HR is related to various elements that influence performance, one of which is compensation. Compensation is an important aspect of a company that must be given to employees because with compensation, employees feel more enthusiastic about completing work more optimally. This research aims to determine the effect of compensation on employee performance at CV Mega Anugerah Kudus. The research method uses quantitative mixed methods to study the relationship between compensation variables and employee performance. The results of this research were obtained from the results of the t (partial) test which showed the value tcount>ttable (2,374 > 1,686), with a significance of 0.023 < 0.05. The research results show that there is a significant positive influence of compensation on the performance of CV employees. Mega Anugerah Kudus.